Analisis Pendapatan Usahatani Kacang Tanah (Arachis Hypogaea, L.) di Kelurahan Wailiti Kecamatan Alok Barat Kabupaten Sikka - Henderikus Darwin Beja; Akbar Saitama (Fakultas Pertanian, Universitas Nusa Nipa, 2025)
The research was conducted in Wailiti Village, West Alok District, Sikka Regency, from May to June 2024. The purpose of this study was to determine the income of peanut farming in Wailiti Village, West Alok District, Sikka Regency. The results showed that the average income was IDR 426,146, with the highest income from peanut farming amounting to IDR 2,284,750 and the lowest income amounting to IDR 25,500. The R/C ratio of peanut farming was 1.5, which, according to the criterion that an R/C ratio greater than 1 indicates feasibility, means that the farming activity is considered economically feasible. Therefore, peanut farming in the research area can be regarded as feasible to operate.